Electric Vehicle Review: BEV, PHEV, HEV, or FCEV? - Kusuma, Idris; Ruliyanta; Kusumoputro, R. A. S.; Iswadi, Agung (Jurnal Konversi Energi dan Manufaktur, 2025)
Electric vehicles (EVs) are rapidly advancing as a sustainable transportation solution in the global effort to reduce carbon emissions. There are four main types of EVs: battery electric vehicles (BEVs), plug-in hybrid electric vehicles (PHEVs), hybrid electric vehicles (HEVs), and fuel cell electric vehicles (FCEVs). This article reviews each EV type's advantages, limitations, and prospects based on energy efficiency, carbon emissions, technological development, and infrastructure readiness. The findings indicate that BEVs hold the most significant potential for personal vehicles and urban transportation, while FCEVs are more suited for heavy-duty and long-distance applications. PHEVs and HEVs are considered transition solutions, but their relevance is expected to decrease as technology and global policies evolve. BEVs provide zero emissions. PHEVs provide high flexibility, while HEVs do not require charging infrastructure, and FCEVs offer zero emissions and long-range and fast charging times. FCEV can travel up to more than 800 KM, which is very promising for the distance travelled problem, which is a challenge for electric vehicles.